Genetic evaluation of Ongole bulls in organized herds in India - SINGH, UMESH; KUMAR, ARUN; ALEX, RANI; VINOO, R (The Indian Journal of Animal Sciences, 2016)
The first lactation records of 123 cows that were daughters of eight bulls were used to evaluate the breeding value of Ongole bulls and to rank them based on single trait analysis. The overall least-squares mean of first lactation milk yield was 622.97±43.82 kg. Nongenetic factors such as year of birth, age at first calving and farm/ herd were found to have significant on first lactation milk yield. Out of eight bulls, five bulls exceeded the herd average and the topmost ranking bull (Bull No. L- 309) had 3.04 % genetic superiority over the population mean followed by Bull No. L- 313 and Bull No.L-306. The frozen semen doses of top ranked bulls are to be used on elite cows to produce future bull calves for inducting into new set (s).